2022
DOI: 10.1177/17455057221087888
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 lockdown on intimate partner violence: Issues of non-reporting in Bangladesh

Abstract: Introduction: COVID-19 pandemic induced lockdown as prevention and control measure, forced people globally to limit their movements and to stay at home for extended period of time. The objective of this study was to analyze the impact of lockdown on intimate partner violence in Bangladesh. Methods: We conducted a secondary research by employing a Poisson regression model to estimate the effect of pandemic-led lockdown policy on the change in the number of intimate partner violence-related calls during pandemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In Spain, the Democratic Republic of Congo, South Africa, Guatemala, India, and Bangladesh, lockdown periods saw increased incidence of, and police reports of, domestic violence against women [167][168][169][170][171][172] . Studies surmise that the official figures for such violence are under-reported as many formal and informal communication channels to access help for the victims, including transport to access shelters in some countries, either shut down or slowed down their operations during the pandemic, fostering change in help-seeking behaviour among abused women 167,169,173 . School closures that force children to be homebound also put them at a higher risk of violence 174 .…”
Section: Victims Of Domestic Violence: Vulnerability and Physical Dis...mentioning
confidence: 99%
See 1 more Smart Citation
“…In Spain, the Democratic Republic of Congo, South Africa, Guatemala, India, and Bangladesh, lockdown periods saw increased incidence of, and police reports of, domestic violence against women [167][168][169][170][171][172] . Studies surmise that the official figures for such violence are under-reported as many formal and informal communication channels to access help for the victims, including transport to access shelters in some countries, either shut down or slowed down their operations during the pandemic, fostering change in help-seeking behaviour among abused women 167,169,173 . School closures that force children to be homebound also put them at a higher risk of violence 174 .…”
Section: Victims Of Domestic Violence: Vulnerability and Physical Dis...mentioning
confidence: 99%
“…Among the countries that have implemented physical distancing measures, few have ringfenced measures for vulnerable groups (e.g., income support for the low-income populations), which suffer from the unintended consequences of physical distancing 204 . Effective control of the COVID-19 pandemic requires packaging policy measures strategically to address multiple competing objectives and to balance • Bangladesh, South Africa, Spain: many channels to help the abused victims had shut down or slowed down in their operations during the pandemic 167,169,173 .…”
Section: Victims Of Domestic Violencementioning
confidence: 99%
“…As found in this study, the measures implemented during the COVID-19 pandemic, especially lockdowns and restrictions and have substantially increased the risk of gender-based violence [ 22 , 27 , 30 , 32 , 36 , 39 , 43 , 50 , 51 , 58 , 61 , 69 , 70 , 75 , 76 ]. Gender and sexual minorities have been severely affected [ 36 , 49 , 56 , 61 , 67 , 70 ].…”
Section: Discussionmentioning
confidence: 87%
“…The implemented policies related to the dimension of asymmetries and inequalities; although they were stated in several texts, they took on a central role in studies specifically addressing gender-based violence (GBV) during the lockdown period ( Table 1 ) [ 22 , 27 , 30 , 32 , 36 , 39 , 43 , 50 , 51 , 58 , 61 , 69 , 70 , 75 , 76 ]. Difficulties in accessing essential services by survivors of GBV, both because they were unable to travel or seek help and because services were reduced during this period, were also reported in these studies [ 22 , 27 , 30 , 32 , 43 , 58 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, this measure inadvertently led to psychological exhaustion, economic downturn, and a surge in sexual violence against Wati, L., Bajari, A., Wahyudin, U., Koswara, I. (2023) women and children, not limited to Indonesia alone but prevalent across the globe (Boserup et al, 2020;Engda et al, 2022;Mahmood et al, 2022). The pandemic-induced economic decline has been linked to increased sexual violence cases (Peitzmeier et al, 2021), and heightened stress and financial instability have been identified as contributing factors to this rise (Cannon et al, 2021).…”
Section: Introductionmentioning
confidence: 99%